Accelerated fragmentation of two thermoplastics (polylactic acid and polypropylene) into microplastics after UV radiation and seawater immersion - Zhiyue Niu; Marco Curto; Maelenn Le Gall; Elke Demeyer; Jana Asselman; Colin R Janssen; Hom Nath Dhakal; Peter Davies; Ana Isabel Catarino; Gert Everaert (Ecotoxicology and Environmental Safety, 2024)
To better understand the fate and assess the ingestible fraction of microplastics (by aquatic organisms), it is essential to quantify and characterize of their released from larger items under environmental realistic conditions. However, the current information on the fragmentation and size-based characteristics of released microplastics, for example from bio-based thermoplastics, is largely unknown. The goal of our work was to assess the fragmentation and release of microplastics, under ultraviolet (UV) radiation and in seawater, from polylactic acid (PLA) items, a bio-based polymer, and from polypropylene (PP) items, a petroleum-based polymer. To do so, we exposed pristine items of PLA and PP, immersed in filtered natural seawater, to accelerated UV radiation for 57 and 76 days, simulating 18 and 24 months of mean natural solar irradiance in Europe. Our results indicated that 76-day UV radiation induced the fragmentation of parent plastic items and the microplastics (50 - 5000 µm) formation from both PP and PLA items. The PP samples (48 ± 26 microplastics / cm2) released up to nine times more microplastics than PLA samples (5 ± 2 microplastics / cm2) after a 76-day UV exposure, implying that the PLA tested items had a lower fragmentation rate than PP. The particles’ length of released microplastics was parameterized using a power law exponent (α), to assess their size distribution. The obtained α values were 3.04 ± 0.11 and 2.54 ± 0.06 (-) for 76-day UV weathered PP and PLA, respectively, meaning that PLA microplastics had a larger sized microplastics fraction than PP particles. With respect to their two-dimensional shape, PLA microplastics also had lower width-to-length ratio (0.51 ± 0.17) and greater fiber-shaped fractions (16%) than PP microplastics (0.57 ± 0.17% and 11%, respectively). Overall, the bio-based PLA items under study were more resistant to fragmentation and release of microplastics than the petroleum-based PP tested items, and the parameterized characteristics of released microplastics were polymer-dependent. Our work indicates that even though bio-based plastics may have a slower release of fragmented particles under UV radiation compared to conventional polymer types, they still have the potential to act as a source of microplastics in the marine environment, with particles being available to biota within ingestible size fractions, if not removed before major fragmentation processes.